2022
DOI: 10.1186/s13195-022-01101-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted telomere length and Alzheimer’s disease endophenotypes: a Mendelian randomization study

Abstract: Telomere length (TL) is associated with biological aging, consequently influencing the risk of age-related diseases such as Alzheimer’s disease (AD). We aimed to evaluate the potential causal role of TL in AD endophenotypes (i.e., cognitive performance, N = 2233; brain age and AD-related signatures, N = 1134; and cerebrospinal fluid biomarkers (CSF) of AD and neurodegeneration, N = 304) through a Mendelian randomization (MR) analysis. Our analysis was conducted in the context of the ALFA (ALzheimer and FAmilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…However, the current study only used a subset of UKB participants and the proxy score may not be an appropriate substitute for clinical LOAD status (17, 68). Despite the high genetic correlation, true LOAD cases in the full UKB sample have higher polygenic risk scores compared to proxy cases (27) and inconsistent results have been attributed to the use of the LOAD proxy score (69). The LOAD-by-proxy score is sensitive to recall bias, because the score is based on self-reported parental information by the participants.…”
Section: Resultsmentioning
confidence: 99%
“…However, the current study only used a subset of UKB participants and the proxy score may not be an appropriate substitute for clinical LOAD status (17, 68). Despite the high genetic correlation, true LOAD cases in the full UKB sample have higher polygenic risk scores compared to proxy cases (27) and inconsistent results have been attributed to the use of the LOAD proxy score (69). The LOAD-by-proxy score is sensitive to recall bias, because the score is based on self-reported parental information by the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have observed associations between shortened LTL and conditions such as Alzheimer’s disease 51 , atherosclerotic diseases 52 , type 2 diabetes 20 , and cancer 53 , which are also relatively common in sepsis patients. Recent research has indicated that biological age holds more therapeutic value than chronological age, as it is believed to offer a more precise prediction of health aging 6 , 8 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…This multifaceted approach enhances our understanding of how molecular differences correlate with in vivo neuroimaging phenotypes 59 . Additionally, our incorporation of techniques such as Mendelian Randomization provides a means to establish causal links between modifiable risk factors and AD pathology, including its subsequent consequences, 60 ultimately influencing the potential to establish primary and secondary prevention strategies during the primary and preclinical stages 61 …”
Section: Discussionmentioning
confidence: 99%